2017
DOI: 10.1016/j.breast.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-sparing and skin-sparing mastectomy: Review of aims, oncological safety and contraindications

Abstract: Skin-sparing (SSM) and nipple-sparing (NSM) mastectomies relatively new conservative surgical approaches to breast cancer. In SSM most of the breast skin is conserved to create a pocket that facilitates immediate breast reconstruction with implant or autologous graft to achieve a quality cosmetic outcome. NSM is closely similar except that the nipple-areola complex (NAC) is also conserved. Meta-analyses indicate that outcomes for SSM and NSM do not differ from those for non-conservative mastectomies. Recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
165
2
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(184 citation statements)
references
References 20 publications
7
165
2
10
Order By: Relevance
“…Patients who are obese or have multiple medical co-morbidities are not ideal candidates for NSM due to the increased risk of complications with complex surgery, reconstruction, and the associated longer operative time. However, in recent years, NSM has been used more widely in groups previously excluded from consideration, for example, in selected patients following neoadjuvant chemotherapy, and in those with prior breast incisions or macromastia 3,7 .…”
Section: Patient Selection and Other Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who are obese or have multiple medical co-morbidities are not ideal candidates for NSM due to the increased risk of complications with complex surgery, reconstruction, and the associated longer operative time. However, in recent years, NSM has been used more widely in groups previously excluded from consideration, for example, in selected patients following neoadjuvant chemotherapy, and in those with prior breast incisions or macromastia 3,7 .…”
Section: Patient Selection and Other Considerationsmentioning
confidence: 99%
“…Preservation of the NAC has been associated with improved body image, satisfaction with nipple appearance and sensitivity, and higher psychosocial and sexual well-being in patients who undergo NSM compared with SSM 1,2 . Recent studies have confirmed the oncologic safety of NSM and its successful application for risk reduction in patients at high risk for breast cancer [3][4][5] . Complication rates in recent years are comparable to those for other types of post-mastectomy reconstruction, likely a result of improving surgeon experience and wider application of NSM technique 3,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic prosthesis has some shortcomings, such as infection of the surrounding tissues, wound dehiscence, capsular contracture, variations in shape, dislocation from the implant site, calcification, or even a further rupture of the prosthesis itself (Galimberti et al, ). In the worst case, the patient requires a replacement of the implant through additional surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal surgical plane provides the surgeon with a better overview of the operative field (12), resulting in adequate resection of breast parenchyma to obtain the best oncological outcome, while retaining the maximum amount of subcutaneous adipose tissue on the skin flaps to achieve the best aesthetic results (7,8,13,14). In this visualized surgery paper, we present our experience identifying the dissection plane using hydrodissection through an inframammary incision.…”
mentioning
confidence: 99%